MARKETING RESEARCH AS AN INFORMATION BASIS FOR THE DIAGNOSTICS OF THE MARKETING ACTIVITY OF THE ENTERPRISE - LARKA, LUDMILA (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the correspondence of marketing research to the information needs of marketing diagnostics of the enterprise. The purpose of the article is to substantiate the expediency of a wider application of marketing research as an information basis for diagnosing the marketing activity of an enterprise in modern economic conditions. It was determined that the application of marketing research ensures the search, processing, accumulation and updating of information through the use of special methods of its processing for the purpose of making management decisions. The possibility of using marketing research as an information basis for diagnosing the marketing activity of an enterprise by analyzing the components of information support is substantiated. Information technologies that can be applied during marketing research are analyzed. A description of interested parties in conducting marketing research is given. An overview of the software products, which are expedient to use for organizing, conducting and processing the results of marketing research, was carried out. The content of the company’s information resources, which are formed based on the results of marketing research, has been studied. It was determined that the algorithm for forming marketing support is related to the algorithm for conducting marketing research, which indicates the possibility of marketing research to act as information support for marketing diagnostics. It was determined that conducting marketing research provides the diagnostic process with such accurate and relevant data as the company’s market share, real and potential market capacity, supply and demand ratio, marketing risks, competitive situation on the market, competitive strategies of market participants, target audience profile, consumer satisfaction product parameters. It is shown that the financing of marketing research is a contribution to the development of the diagnostic information base, which will have a long-term economic effect.